Pharmacokinetics and urinary excretion of ciprofloxacin in crossbred cow calves - SINGH, K; SRIVASTAVA, A K (The Indian Journal of Animal Sciences, 2014)
The pharmacokinetics, urinary excretion and dosage regimen of ciprofioxaein after it’s single intravenous administration of 5 mg.kg -1 was investigated in crossbred cow calves. At 1 min the concentration of ciprofloxacin in plasma was 10.3 Â± 0.10 pg.ml which rapidly declined to 3.07 Â± 0.02ug.ml-1 at 10 min. The minimum therapeutic concentration (0.1 ugml-1) in plasma was maintained lip to 6 hr. The elimination half life and volume of distribution were 3.75 Â± 0.06 hr and 6.80 Â± 0.15 L.kg -1. respectively. The distribution half life and AUC were 0.21 Â± 0.003 hr and 3.98 Â± 0.05ug.ml -1 hr respectiVely. The total body clearance (CIa) and tissue/plasma T/P) ratio werc 1.24 Â± 0,02 L.kg’hr and 8.01 Â± 0.22 respectively. Approximately 18% of the total administered dose ofciprofloxacin was recovered in urine within 24 hr after administration. A satisfactory intravenous dosage regimen of ciprotloxacin in cow calves would be 6 mg. kg -1 followed by 5 mg kg-1 repeated at 12 hr intervals.